Association between Water-Based Lubricant Use and Condom Failure among Young Men Sex with Men (MSM) in Indonesia - Mamoribo, Sherly Novita; Fatiah, Mona Safitri (IAKMI South Tangerang Branch, 2025)
Background: In Indonesia, water-based lubricant use among men who have sex with men (MSM) is lower than that reported in transgender populations (84.4%). This study examined the association between water or gel based lubricant use and condom failure, defined as leakage or breakage, among young MSM. Methods: Data were drawn from the 2018–2019 Integrated Biological and Behavioral Survey (IBBS), a cross-sectional survey in 24 provinces. Of 6,000 MSM, 2,213 respondents aged 15–25 years were recruited using Respondent Driven Sampling (RDS). Logistic regression in STATA 16 assessed associations, adjusting for circumcision status and number of male sexual partners. Results: Condom failure in the past month was reported by 8.8% of respondents, and 66.3% used water-based lubricants. Non-use of water- or gel-based lubricants was associated with higher adjusted odds of condom failure, but not statistically significant (AOR 1.79; 95% CI 0.79–4.05). Condom failure was more common among those reporting more male clients. Circumcision status was also related, with lower odds of failure among uncircumcised participants. Conclusions: Water-based lubricant use was not significantly linked to reduced condom failure. Improving condom-use skills, promoting compatible lubricants, and targeting MSM with multiple partners remain important for reducing condom failure and HIV/STI risks.